2009
DOI: 10.3960/jslrt.49.9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Antibody Reaction for the Primary Antigen but not for the Recall Antigen of Influenza Vaccination in Patients with Non-Hodgkin B-Cell Lymphoma after the Administration of Rituximab-CHOP

Abstract: To assess the humoral response to the influenza vaccine in patients undergoing R-CHOP therapy (rituximab combined with cyclophosphamide, doxorubicin, vincristine, and predonisolone) for non-Hodgkin lymphoma (NHL), the anti-hemagglutinin (HA) titer in 7 NHL patients undergoing therapy was compared with those in 10 control group subjects in the 2005/2006 season. Four weeks after vaccination, the HA titers against the influenza type A H1N1 and type B antigens, the same antigens that had been used in the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 12 publications
6
27
0
2
Order By: Relevance
“…Prior rituximab therapy completely abrogated subsequent vaccination response in our cohort, which is in line with other results reported elsewhere [13,22,28,29]. Moreover, a patient receiving rituximab as the sole immunosuppressive treatment 8 months before being vaccinated against pandemic H1N1 (2009) virus developed life-threatening pandemic H1N1 (2009) infection despite vaccination, indicating a long-lasting effect of rituximab.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Prior rituximab therapy completely abrogated subsequent vaccination response in our cohort, which is in line with other results reported elsewhere [13,22,28,29]. Moreover, a patient receiving rituximab as the sole immunosuppressive treatment 8 months before being vaccinated against pandemic H1N1 (2009) virus developed life-threatening pandemic H1N1 (2009) infection despite vaccination, indicating a long-lasting effect of rituximab.…”
Section: Discussionsupporting
confidence: 91%
“…A very poor response to seasonal influenza vaccination in patients treated with monoclonal antibodies (rituximab or alemtuzumab) for lymphoma has been described by Ljungman et al [26] and confirmed in patients with rheumatoid arthritis [31]. Whether recall antigens can generate an appreciable response to influenza vaccination in patients after rituximab therapy, as described by Takata et al, was not examined in our cohort [29].…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies have also shown the low immunogenicity of influenza vaccines in lymphoma patients and patients on rituximab treatment. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] The results obtained by us here are in agreement with those findings. Subjects having pre-titer ≥ 1:10 did not show any increase in antibody response after the second vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…21 Although the effect of rituximab on the immunogenicity of seasonal influenza vaccination remains unclear, 14,22 it has been suggested that rituximab negatively affects the ability to respond to novel influenza antigens. 22 Indeed, we recently showed that patients treated with rituximab with confirmed H1N1 infection fail to mount an antibody response to H1N1. 9 In our current study none of the patients treated with rituximab within 6 months of vaccination achieved detectable antibody titers to H1N1.…”
Section: Discussionmentioning
confidence: 99%